EFFECT OF EXCESSIVE GESTATIONAL WEIGHT GAIN ON PREGNANCY OUTCOME: A CASE STUDY OF TERTIARY HOSPITALS IN BENUE STATE, NIGERIA - Nwaogwugwu, Amarachi; Simeon, Nwabueze Achunam; Ekwuluo, Celestine E (International Journal of Research -GRANTHAALAYAH, 2020)
Motivation/Background: Little is known of adverse pregnancy outcomes resulting from Excess Gestational Weight Gain (EGWG) in Benue state, Nigeria. In this study, we aimed to assess the effects and association of EGWG on pregnancy outcome in tertiary hospitals in Benue State. Method: We used retrospective cohort study to examine the data obtained from the general Antenatal Care (ANC) Register of 350 pregnant women who attended ANC clinic between January 1, 2016 and December 31, 2016. Pre-pregnancy Body Mass Index (BMI) was calculated by dividing weight in kilograms within first 14 weeks of gestation by square of height in meters while total gestational weight was calculated as difference between weight before, or at 14 weeks and weight at 37 weeks of gestation prior to delivery. Results: Data analysis was done using SPSS version 21. Out of the sampled folders, 103 (29.4%) women gained excess weight during pregnancy, 130 (37.1%) women gained the recommended weight while 117 (33.4%) women gained weight less than the recommended value. Analysis showed strong association between EGWG and pregnancy induced hypertension/pre-eclampsia, caesarean section and macrosomia. Conclusions: The study concluded that EGWG should be avoided by educating women on the need to gain appropriate weight during pregnancy to prevent adverse pregnancy outcomes which affect both mothers and their offspring.